Lower limb symmetry index (LLSI) pre- and post-reconstruction of the ACL: a controlled study - Lustosa, Luma Soares; Pereira, Nyck Douglas Claro; Ferreira, José Jamacy de Almeida; Andrade, Palloma Rodrigues de; Santos, Heleodório Honorato dos (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: The anterior cruciate ligament (ACL) lesion causes a deficit in joint stability and mobility, trophism and muscular strength, generating asymmetries between the lower limbs. Objective: To verify the effect of a physiotherapeutic protocol on the Lower Limb Symmetry Index (LLSI) and the correlation between strength and EMGs, pre and post reconstruction of the ACL. Methods: Twenty subjects (10 ACLrg + 10 CONTg) were evaluated regarding isometric force and electrical activity of knee extensors, knee flexors and hip abductors. Results: A significant increase (P<0.01) in knee extension and flexion strength and hip abduction strength were observed both for the affected limb and non-affected limb. Regarding the LLSI, a significant increase was observed for knee extension and hip abduction movements in the pre- and post-treatment comparison, and between ACLrg X CONTg (P<0.01) for the knee extension movement in the pre-reconstruction phase of the ACL. A very strong correlation (r=0.945; P<0.01) was also observed between the LLSI strength X EMGs during knee extension, pre- and post-reconstruction surgery. Conclusions: Six months after reconstruction of the ACL, there was an increase in strength and EMG activity of the knee flexor, knee extensor and hip abductor muscles, leveling the LLSI between ACLrg and the CONTg, however, with a significant correlation between the two variables (strength X EMGs) for only one of the three movements (knee extension).